2021
DOI: 10.1111/jcmm.16967
|View full text |Cite
|
Sign up to set email alerts
|

Cancer testis antigen PRAME: An anti‐cancer target with immunomodulatory potential

Abstract: PReferentially expressed Antigen in Melanoma (PRAME) is a cancer testis antigen with restricted expression in somatic tissues and re‐expression in poor prognostic solid tumours. PRAME has been extensively investigated as a target for immunotherapy, however, its role in modulating the anti‐tumour immune response remains largely unknown. Here, we show that PRAME tumour expression is associated with worse survival in the TCGA breast cancer cohort, particularly in immune‐unfavourable tumours. Using direct and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…In recent years, great research interest has been directed to the diagnostic, therapeutic and marker role of Preferentially expressed Antigen in Melanoma (PRAME) in the setting of various human neoplasms [ 1 , 2 ]. First discovered and described in 1997 by Ikeda H. et al, in an autologous T lymphocytes clone in a patient with metastatic cutaneous melanoma, PRAME has returned to the attention of researchers both in the context of possible immunotherapies [ 3 , 4 ] and its diagnostic role in lesions mainly of a melanocytic nature [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great research interest has been directed to the diagnostic, therapeutic and marker role of Preferentially expressed Antigen in Melanoma (PRAME) in the setting of various human neoplasms [ 1 , 2 ]. First discovered and described in 1997 by Ikeda H. et al, in an autologous T lymphocytes clone in a patient with metastatic cutaneous melanoma, PRAME has returned to the attention of researchers both in the context of possible immunotherapies [ 3 , 4 ] and its diagnostic role in lesions mainly of a melanocytic nature [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their expression pattern, CTAs have been attractive as cancer-speci c therapeutic targets. The immunogenicity of some CTAs was identi ed, suggesting that these CTAs could be applied in cancer immunotherapy [13,19,20]. Until now, several targeted immunotherapies for CTAs have been developed, and these immunotherapies have been tested in preclinical and early clinical trials [21].…”
Section: Discussionmentioning
confidence: 99%
“…PRAME is frequently expressed in various solid tumors, such as head and neck cancer and non-small-cell lung cancer NSCLC [11,12]. PRAMEbased vaccines and adoptive T cell therapies have shown a favorable safety pro le and e cient induction of potent immune responses in tumors [13]. Kita-Kyushu Lung Cancer antigen-1 (KK-LC-1), also known as CT83, is expressed in different types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Another extensively investigated target CTA for immunotherapeutic strategies is PRAME. Most studies on PRAME as an immune environment modulator implicate a negative correlation between the expressions of PRAME and antigen-presenting molecules as well as immune checkpoint molecules such as PD-1, LAG3 (lymphocyte-activation gene 3), PD-L1(programmed death-ligand 1), CD86 (cluster of differentiation 86), Gal-9 (galectin-9) and VISTA (V-domain Ig suppressor of T-cell activation) [ 185 , 186 , 187 , 188 ]. This implies that PRAME expression may be involved in immune escape mechanisms during carcinogenesis and may potentially indicate an immune cold tumour environment.…”
Section: Cta Biology In Carcinogenesismentioning
confidence: 99%
“…Thus, modulation of PRAME expression is considered a viable strategy to improve the efficacy of immune checkpoint inhibitors in cancers. Interestingly, PRAME tumour expression was shown to suppress the expression and secretion of multiple proinflammatory cytokines and mediators of T-cell activation, differentiation and cytolysis during inflammation [ 185 ], further highlighting the role of PRAME in regulating immune activation in the tumour microenvironment (TME). Of note, a recent study by Takata et al demonstrated that in patients with diffuse large B-cell lymphoma (DLBCL), PRAME -deleted tumours showed cytotoxic T-cell immune escape and were associated with cold tumour microenvironments with the enhancer of zeste homolog 2–activating (EZH2-activating) mutations suppressing PRAME expression.…”
Section: Cta Biology In Carcinogenesismentioning
confidence: 99%